2006
DOI: 10.1007/s11423-006-9603-3
|View full text |Cite
|
Sign up to set email alerts
|

Type of Positive Interdependence and Affiliation Motive in an Asynchronous, Collaborative Learning Environment

Abstract: In this study, we investigated the effect of type of positive interdependence (roles, rewards, roles-plus-rewards, or Keywords: Cooperative learning, positive interdependence, affiliation, social orientation, roles, rewards, online, asynchronous, distance learning Over the past decade, there has been increased research on using small group methods with college students and other adult learners. According to Johnson, Johnson, and Smith (1998a), the results of this research are impressive when the magnitude of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(62 citation statements)
references
References 37 publications
5
54
0
3
Order By: Relevance
“…Higher explicit motive scores have also been found in team players compared to athletes in individual sports (Elbe et al, 2013;Teubel, 2012). Thus, results of this present study fit in with findings of stronger need for friendly relationships (Wong & Csikszentmihalyi, 1991), higher self attributed coopera tiveness and sociability (Elbe et al, 2013), and more positive atti tudes and concern for teammates (Brewer & Klein, 2006) found for individuals with a high explicit affiliation motive. Nonverbal social behavior, in contrast, was associated with in direct measures of the implicit affiliation motive.…”
Section: Overallsupporting
confidence: 85%
See 1 more Smart Citation
“…Higher explicit motive scores have also been found in team players compared to athletes in individual sports (Elbe et al, 2013;Teubel, 2012). Thus, results of this present study fit in with findings of stronger need for friendly relationships (Wong & Csikszentmihalyi, 1991), higher self attributed coopera tiveness and sociability (Elbe et al, 2013), and more positive atti tudes and concern for teammates (Brewer & Klein, 2006) found for individuals with a high explicit affiliation motive. Nonverbal social behavior, in contrast, was associated with in direct measures of the implicit affiliation motive.…”
Section: Overallsupporting
confidence: 85%
“…Other researchers found that sport students' self attribution of personal cooperativeness and sociability are linked to measures of the explicit affiliation motive (Elbe, Krippl, Melzer, & Teubel, 2013). Moreover, people with a high explicit affiliation motive display a more positive attitude toward giving and receiving in a team, and show greater concern for their teammates (Brewer & Klein, 2006). The explicit motive is thus predominantly reflected in how much a person values social interaction.…”
Section: The Explicit Vs Implicit Affiliation Motivementioning
confidence: 98%
“…Many studies have suggested that proper use of asynchronous online discussion in conventional formal learning environments engages learners and improves performance (Brewer & Klein, 2006;Chen & Chiu, 2008;Cheung & Hew, 2004;Hew et al, 2010;Khine, Yeap, & Chin Lok, 2003;Oliver & Shaw, 2003). Learners in these studies had similar backgrounds; for example, all learners were pre-service teachers (Cheung & Hew, 2004;Hew et al, 2010;Khine et al, 2003;Vonderwell, 2003) or had similar academic backgrounds: business (Brewer & Klein, 2006), mathematics (Chen & Chiu, 2008) and health science (Masters & Oberprieler, 2004;Oliver & Shaw, 2003).…”
Section: Asynchronous Online Discussion Forum Activities and Cognitivmentioning
confidence: 99%
“…Learners in these studies had similar backgrounds; for example, all learners were pre-service teachers (Cheung & Hew, 2004;Hew et al, 2010;Khine et al, 2003;Vonderwell, 2003) or had similar academic backgrounds: business (Brewer & Klein, 2006), mathematics (Chen & Chiu, 2008) and health science (Masters & Oberprieler, 2004;Oliver & Shaw, 2003). Therefore, literature on online forum use has focused on investigating how to engage student participation in closed asynchronous online discussions (e.g., Dennen, 2005;Hew et al, 2010;Masters & Oberprieler, 2004;Vonderwell, 2003).…”
Section: Asynchronous Online Discussion Forum Activities and Cognitivmentioning
confidence: 99%
“…El aumento en disponibilidad de las nuevas tecnologías sugiere que la formación de los maestros puede ser fundamentalmente distinta a enfoques previos (Brewer & Klein, 2006). Aprender a enseñar exige una nueva manera de aprender.…”
Section: Implicaciones Recomendaciones E Investigaciones Futurasunclassified